Exploring the driving factors behind traditional food entrepreneurs in Sabah and Selangor - Adilah Md Ramli; Harifah Mohd Noor; Mazni Saad; Joko Sulistyo (AMER ABRA cE-Baby e-International Publishing House, Ltd, 2024)
This study explores the key factors influencing local entrepreneurs in Sabah and Selangor states in selling traditional food. Twenty (20) informants from various business categories are identified and interviewed using a qualitative method. The transcript interview is being analysed to develop code and theme. Results showed there are two (2) themes that have been identified: 1) criteria for traditional food (cooking method, flavour, and originality) and 2) demand for traditional food (history, origin of food). Findings show the key factors that drive local entrepreneurs to develop distinctive attractions and become new tourism destinations, especially in traditional food areas.